2022
DOI: 10.1002/cam4.5096
|View full text |Cite
|
Sign up to set email alerts
|

IGF2BP2 promotes pancreatic carcinoma progression by enhancing the stability of B3GNT6 mRNA via m6A methylation

Abstract: BackgroundPancreatic carcinoma (PC) is a highly lethal cancer with an increasing mortality rate, its ve-year survival rate is only approximately 4%. N6-methyladenosine (m6A) modi cation is the most common posttranscriptional modi cation of RNA. However, its role in PC remains unclear. MethodsWe combined bioinformatic analysis with in vitro and in vivo experiments to investigate the expression pro le of methylation modulators and identify key m6A regulators in the progression of PC. Further study focused on exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 66 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…Previous study had suggested that IGF2BP2 elevated FLT4 stability via m6A modification, thus accelerating angiogenesis and metastasis of lung adenocarcinoma cells [ 36 ]. Also, IGF2BP3 promoted pancreatic carcinoma cell proliferation and migration by improving B3GNT6 mRNA stability [ 37 ]. Here, we pointed out that IGF2BP2, as an m6A reader, recognized and bound to the m6A modified region of NRP1 transcript to enhance NRP1 mRNA stability.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study had suggested that IGF2BP2 elevated FLT4 stability via m6A modification, thus accelerating angiogenesis and metastasis of lung adenocarcinoma cells [ 36 ]. Also, IGF2BP3 promoted pancreatic carcinoma cell proliferation and migration by improving B3GNT6 mRNA stability [ 37 ]. Here, we pointed out that IGF2BP2, as an m6A reader, recognized and bound to the m6A modified region of NRP1 transcript to enhance NRP1 mRNA stability.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, only the high expression of IGF2BP2 and IGF2BP3 was linked to poor prognosis in PAAD. As the stabilizers of m 6 A methylation, IGF2BP2 and IGF2BP3 can enhance the stability of B3GNT6 and spermine synthase ( SMS ) mRNA and protein expression, respectively, to promote the progression of pancreatic cancer [ 39 , 40 ]. In light of these findings, we proposed that the FERMT1 may be modified by m 6 A to enhance mRNA stability, thereby accelerating the development of PAAD.…”
Section: Discussionmentioning
confidence: 99%
“…B3GNT6, the protein that is essential for the synthesis of the core 3 structure of O-glycans, has been documented to be commonly dysregulated in many types of malignant tumors such as cervical cancer, prostate cancer and CRC 31 . Cao et al, showed that the oncogenic role of IGF2BP2 was mediated by modulating B3GNT6 mRNA stability 32 . Accordingly, B3GNT6 can affect EMT-MTE plasticity of CRC cells.…”
Section: Discussionmentioning
confidence: 99%